Klasifikasi Akad Tabarru’: Implementasi Akad Qardh Atas Take Over Di Bank Syariah Indonesia - Ayu, Dena; Arzam, Arzam; Witro, Doli (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
This article discusses the classification of tabarru’ contracts and the implementation of qardh contracts on the take over in Indonesian Islamic banks. The research method used in this article was qualitative research method. Data were collected by using literature study technique. Data were collected from several sources as references such as books, articles, and other data sources. Data analysis techniques used were data condensation, data presentation, and drawing conclusions. This article reveals that the tabarru’ contract is a contract that is applied with the concept of helping each other in order to achieve goodness. There are several classifications of tabarru’ contracts, namely the concept of guaranteeing money (qardh, rahn, hiwalah), guaranteeing oneself (kafalah, wakaalah, wadi’ah) and giving something (hibah, hadiah, wakaf, ZIS). This classification makes it easy to understand the concepts and implementation of the tabarru contract in life, but still prioritize the common good. The implementation of the qardh contract on the take over at Bank Syariah Indonesia provides convenience to customers who need assistance in transferring debt to conventional financial institutions. The existence of qardh facilities on the principle of helping each other remains sticking to the rules of the Sharia. Artikel ini membahas tentang klasifikasi akad tabarru’ serta implementasi akad qardh atas take over di bank syariah Indonesia. Metode penelitian yang digunakan dalam artikel ini yaitu metode penelitian kualitatif. Teknik pengumpulan data menggunakan cara studi kepustakaan. Data dikumpulkan dari beberapa sumber untuk dijadikan referensi seperti buku-buku, artikel, dan sumber data yang lainnya. Teknik analisis data yang digunakan adalah kondensasi data, penyajian data, dan penarikan kesimpulan. Artikel ini mengungkapkan bahwa akad tabarru’ merupakan akad yang diterapkan dengan konsep saling tolong menolong dalam rangka mencapai kebaikan. Ada beberapa klasifikasi akad tabarru’ yaitu konsep menjamin uang (qardh, rahn, hiwalah), menjamin diri (kafalah, wakaalah, wadi’ah) dan memberikan sesuatu (hibah, hadiah, wakaf, ZIS). Klasifikasi tersebut memberikan kemudahan untuk memahami konsep-konsep dan pengimplementasian akad tabarru’ dalam kehidupan, dengan tetap mengedepankan kemaslahatan bersama. Implementasi akad qardh atas take over di Bank Syariah Indonesia memberikan kemudahan terhadap nasabah yang membutuhkan bantuan terhadap pengalihan hutang terhadap lembaga keuangan konvensional. Adanya fasilitas qardh atas prinsip tolong menolong dengan tetap berpegang teguh pada aturan syariat.